Reindeer (Rangifer tarandus) response to feces and urine from sheep (Ovis aries) and reindeer - Moe, Stein R.; Holand, Øystein; Colman, Jonathan E.; Reimers, Eigil (Rangifer, 1999)
In many Norwegian alpine and tundra areas sheep and reindeer graze sympatrically. Areas covered with dung or urine may have consequences for reindeer pasture utilization. Experiments were conducted on 5 stall fed male reindeer calves where animals were individually presenred with two troughs (experimental and control) containing 200 g of concentrate. Fresh and dry sheep and reindeer pellets (50 g wet weight) were mixed with the concentrate in the experimental trough and the aversive response was tested against the control. Both fresh sheep (P < 0.0001) and reindeer (P < 0.0001) pellets were associated with aversive response by reindeer. A similar response was found for dry sheep (P = 0.006) and dry reindeer (P = 0.0009) pellets. Similar trials were conducted using sheep and reindeer urine (20 g sprayed evenly on the food) and the aversive response by reindeer was tested against the control (sprayed with 20 g of water). Both sheep and reindeer urine stimulated an aversive response by reindeer {P = 0.03 for both tests). The differences in the aversive response of reindeer ro fresh sheep and reindeer pellets, dry sheep and reindeer pellets and sheep and reindeer urine were also tested. No differences by reindeer were found between sheep and reindeer pellets, either for fresh (P = 0.28) or dry (P = 0.07), or between food treated with sheep and reindeer urine (P = 0.28). Possible habituation to sheep and reindeer pellets was tested using 8 consecutive trials with dry pellets, followed by 2 additional trials when dry pellets were soaked in water. This was done to simulate natural dry periods followed by rain showers. Habituation effects were found in trials with dry sheep and reindeer pellets. Subsequent trials with fecal pellets soaked in water significantly reduced food intake when compared with the last habituation trial with dry pellets (P < 0.05).